Media credibility perception among millennials in Slovakia - Lucia Vilcekova (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2016)
Communication professionals have been facing various challenges and one of them is how to win the audience. Past studies suggest that credibility could be the key. Therefore, credibility can be suggested as one of the key factors driving the traffic of individuals to certain media. By gaining a better understanding of how Millennials perceive credibility, companies can more appropriately plan and execute successful media campaigns directed to this very important public. A survey with 190 respondents - Millennials - was conducted to determine how they perceive the credibility of various media types. To measure the perception of media credibility, 12 characteristics like objectiveness, activity, intelligence, professionalism, etc. were examined. The results of the study revealed general moderate credibility of newspapers and television. The most credible medium for the Millennials is the Internet, especially because of its activity, ability to act fast, independence and objectivity. On the other hand, this cohort sees both television and newspapers as better presented than the Internet. The worst rated feature of television and newspapers was their passivity and political background. When examining statistically significant difference in overall perception, based on the results from the Wilcoxon signed-rank test, we can conclude that the difference in perception of television, newspapers and the Internet was unlikely to occur by chance and the Millennials perceive the Internet as significantly more credible than television and newspapers.
Keywords: M31; M39; 650; media; credibility; Millennials